2009
DOI: 10.1002/cphc.200900023
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable Control of Interfacial Rheology and Emulsion Coalescence

Abstract: Breaking point: Switchable peptide surfactants are used to demonstrate that the extent of cross-linking in an interfacial surfactant layer can control the rate of emulsion coalescence. Pictured is the rupture of an aqueous thin film where the peptide layer lacks sufficient strength to prevent hole formation, but nonetheless dramatically slows the rate of hole expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 24 publications
(27 reference statements)
1
42
0
Order By: Relevance
“…These states can be interconverted by simple manipulation of pH or metal ion concentration (Dexter et al, 2006;Dexter and Middelberg, 2007). Malcolm et al (2009) have examined these peptide surfactants in a microfluidic device and have shown triggered control of coalescence, which was also related to changes in the rupture behavior of the thin film between interfaces. This novel interfacial rheology control offers a new strategy for controlling the stability of emulsions or foams, and also affords a new level of control over droplet coalescence in microfluidic devices.…”
Section: Interfacial Rheology Controlmentioning
confidence: 98%
“…These states can be interconverted by simple manipulation of pH or metal ion concentration (Dexter et al, 2006;Dexter and Middelberg, 2007). Malcolm et al (2009) have examined these peptide surfactants in a microfluidic device and have shown triggered control of coalescence, which was also related to changes in the rupture behavior of the thin film between interfaces. This novel interfacial rheology control offers a new strategy for controlling the stability of emulsions or foams, and also affords a new level of control over droplet coalescence in microfluidic devices.…”
Section: Interfacial Rheology Controlmentioning
confidence: 98%
“…Loss of film cross-linking resulted in rapid emulsion coalescence or foam collapse. 18,19,191,192 Neutron reflectometry showed AM1 concentration at the interface is not significantly altered by film formation or loss. This indicated that the switching of emulsion and foam stabilisation is due to loss of the mechanical properties of the interfacial film rather than surfactant desorption.…”
Section: Surfactantsmentioning
confidence: 95%
“…132 The surfactant properties of a series of reversibly cross-linkable α-helical peptides based on the sequence of Lac21 has been well studied, predominantly by the Middelberg group. 18,19,191,192 Peptide AM1 was designed based on the sequence of Lac21, where residues 9 and 20 were replaced with histidine 24 residues. 18,191 This positioning leaves the histidine residues facing the aqueous phase, but oriented towards neighbouring helices at the interface.…”
Section: Surfactantsmentioning
confidence: 99%
See 2 more Smart Citations